UTILIZATION OF SAGO DREGS AS RUMINANT FEED BY USING THE FERMENTATION METHOD: LITERATURE REVIEW - Titi Lahanda Susanti (BRIN - Badan Riset dan Inovasi Nasional, 2022)
Every year there is a change in the stock of ruminant feed that occurs in the rainy season and water shortages in the dry season. Utilization of agricultural waste as an alternative feed is one way to overcome these problems. One of the wastes that have the potential to be used as feed ingredients is sago waste. Sago pulp is a waste that is rich in lignocellulose, namely cellulose. Several biotechnology applications in ruminant feed fermentation can improve properties such as taste, aroma, shelf life, texture and nutritional value of food. Fermentation using mold or yeast, as well as bacteria or a mixture of various microorganisms can increase the nutrients in the feed needed by ruminant feed. Processing of lignocellulosic materials is required to obtain optimal degradation results. The degradation process will convert lignocellulosic material into raw materials that are easily digested by the ruminant. Enzymes produced by microorganisms can increase crude protein, crude fat, carbohydrates, crude fiber, vitamins and minerals. Thus, the fermentation method of sago dregs and its use as feed can increase the nutritional value, so that productivity can be increased when given as feed.